Interplanetary Ion Flux Dropouts Across Multiple 3He-Rich Events - Ho, G. C.; Mason, G. M.; Allen, R. C.; Wimmer-Schweingruber, R. F.; Rodríguez-Pacheco, J.; Gómez-Herrero, R. (Frontiers in Astronomy and Space Sciences, 2022)
Solar Orbiter, a joint ESA/NASA mission, is studying the Sun and inner heliosphere in greater detail than ever before. Launched in February 2020, Solar Orbiter has already completed its first three orbits, reaching perihelia of 0.5 au from the Sun in June 2020, February and August 2021. During the first two years in orbit, Solar Orbiter observed multiple 3He-rich Solar Energetic Particle (SEP) events inside 1 au. Even though these events were small, their spectral forms, 3He content, and association with energetic electrons and type III bursts convincingly identifies them as 3He-rich SEP events with properties similar to those previously observed at 1 au, and promising new insights as Solar Orbiter moves much closer to the Sun in 2022. In May 2021, we observed six 3He-rich SEP events in close succession within 48 hours when Solar Orbiter was at 0.95 au. These events were likely released from the same active region at the Sun, and the particles arrived at Solar Orbiter in two batches with various abundances and intensities, showing strong anisotropies throughout. Multiple ion flux dropouts were also observed with these six 3He-rich SEP events. The fact that we observed so many ion injections in such a short period of time indicates the 3He enrichment and acceleration mechanism can produce SEP from the same region very efficiently and with varying enrichment levels and intensities. In addition, we report for the first-time dropout features that spanned multiple ion events simultaneously. This implies the field line random walk that we observe at 1 au still maintains magnetic connections to a small region back at the Sun up to the entire duration of these events (~48 hours).